CMOS digital integrated circuits : a first course - Hawkins, Charles F.; Segura, Jaume; Zarkesh-ha, Payman (Materials, Circuits & Devices., 2013)
This undergraduate textbook for electrical and computer engineering students is dedicated solely to digital CMOS electronics. It covers many of the topics of graduate level textbooks, but in an introductory style specifically crafted (and course tested) for undergraduates. Students will not need a prerequisite in analog electronics, allowing instructors flexibility in course scheduling. This book blends the academic and industrial experience of the authors to define a base of electronics instruction for the CMOS chip industry. CMOS Digital Integrated Circuits: A First Course teaches the fundamentals of modern CMOS technology by focusing on central themes and avoiding excessive details. Extensive examples, self-exercises, and end-of-chapter problems assist in teaching the current practices of industry and subjects taught by graduate courses in microelectronics. Computer engineering curriculums can remove the analog electronics prerequisite altogether when adopting this book. Key Features: CMOS technology written specifically for (and tested by) undergraduates; Equal treatment to both types of MOSFET transistors that make up computer circuits; Power properties of logic circuits; Physical and electrical properties of metals; Introduction of timing circuit electronics; Introduction of layout; Real-world examples and problem sets.